Comparative Study of Traditional and Next Generation IPS - Nadir Ali, Mohammed; Mohd Saudi, Madihah; Bhuiyan, Touhid; Abu Bakar, Azreena (International Journal of Engineering and Technology, 2018)
Currently, cyber threats and attacks become a main concern among Internet users. To detect and prevent new and unknown attacks, an intelligent intrusion prevention system (IPS) which is better compared with traditional systems is needed. Furthermore, the Next Generation Intrusion Prevention System (NIGPS) is more suitable that could provide an intelligent IPS solution for new and unknown attacks. Therefore, this paper presents the limitation of traditional IPS systems, a comparison between IPS and NIGPS and proposes an enhanced model for NIGPS.Â Â